The new Dutch sandwich: The issue of treaty abuse - George Kahale (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2011)
Years ago, international tax lawyers introduced us to the term "Dutch sandwich." The concept was to sandwich a Dutch company between an investor from country A and its investment in country B. The combination of the extensive network of Dutch tax treaties and investor-friendly domestic Dutch tax law meant that country A's investor could reduce withholding tax on dividends out of country B and perhaps eliminate capital gains tax altogether by structuring its investment through a Dutch company.
Keywords: 330